LIMITATION OF PARENTAL CONSENT IN RESPECT OF VACCINATIONS IN SOUTH AFRICA: GUIDANCE FROM THE UNITED KINGDOM AND THE UNITED STATES - Khan, Franaaz (Obiter, 2023)
For decades, immunisation has saved millions of lives in South Africa and prevented countless illnesses and disabilities in South Africa. Vaccination is the most important thing we can do to protect ourselves and our children against ill health. One example is paediatric immunisation, which prevents approximately three million child deaths worldwide each year and saves 750 000 more from disability. In addition to alleviating suffering and the prevention of infectious diseases by vaccination, it is also more cost-effective than treatment of infectious diseases once contracted. Nonetheless, the current vaccine climate is polarised, with some vaccine hesitancy in the population. Another conundrum that arises is the vaccine gauntlet between parent and child. The Department of Health announced in 2021 that children are to be vaccinated in South Africa with or without parental consent. In the context of our law and the requirements of informed consent, a child as young as 12 years of age can be vaccinated, unassisted. Several issues and concerns arise in the given circumstances: in one instance there might be an implied threat that a parent’s wish will be undermined and circumvented by the Department of Health and, in another, that a child’s own wish to be vaccinated or not will be ignored. This article examines the conflict over parent and child consent in relation to the Covid-19 vaccination. The current legal framework regarding minors’ consent in South Africa is discussed. Thereafter, the article analyses the consent in respect of children required for the Covid-19 vaccination in the United Kingdom and the United States. The article concludes by exploring recommendations to bridge the divide that exists between parent and child when they have opposing views on vaccinations in certain instances.